El «Padre nuestro» (Mt 6,9-13): significado y valor - Mendoza L.C., Pedro (Alpha Omega, 2017)
Summary: As the various and abundant episodes of the life of Jesus attest, in the Lord’s Prayer that voice resounds, which is that of the praying Son, who not only taught this prayer to his disciples, but who "lived" this prayer in himself. This article seeks to deepen the meaning of the Lord’s Prayer and to see that the example of Jesus praying in this way is to be found in this prayer, along with all his teaching about God the Father.Sommario: Come diversi e abbondanti episodi della vita di Gesù attestano, nella Preghiera del Signore risuona la voce del Figlio orante, che ha “vissuto” questa preghiera e non solo l’ha insegnata ai suoi discepoli. Questo articolo cerca di approfondire il significato della Preghiera del Signore e di vedere come in questa preghiera ritorna l’esempio di Gesù, che prega in questo modo, così come tutto il suo insegnamento su Dio Padre.Key words: Matthew 6:9-13, prayer, Our Father, Lord’s Prayer, petitions in prayer, the meaning of prayer, the value of prayer.Parole chiave: Matteo 6,9-13, preghiera, Padre Nostro, preghiera di Gesù, richieste nella preghiera, significato della preghiera, valore de la preghiera.